User Interface and User Experience (UI/UX) Design Of Scholar East Based on Design Thinking - Alia Mega Putri; Aldino, Ravendiartha Muchlas; Kamulya, Hidayah; Ginasta, Nava Gia (Journal of Digital Business and Innovation Management, 2026)
This study aims to design the user interface (UI) and user experience (UX) for the Scholar East application using the Design Thinking method. This approach is used to facilitate students and scholarship seekers in finding educational opportunities. The research method consists of five stages: Empathize, Define, Ideate, Prototype, and Test. The Empathize stage involved distributing questionnaires to 35 respondents and conducting interviews with 2 respondents to identify user needs. These needs were then analyzed using the Kano Model in the Define stage. The result of this research is a UI/UX design prototype which was evaluated using Usability Testing. The usability testing was conducted using the System Usability Scale (SUS) with 21 respondents. The findings show an average SUS score of 77.88. This score indicates that the Scholar East application is categorized as “Good” to “Excellent” and is capable of meeting user needs for efficiently exploring scholarship information.